Politics in local government in Sarawak - Faisal S. Hazis; Stanley Bye Kadam Kiai (Kota Samarahan, Sarawak : Universiti Malaysia Sarawak, 2013)
This book addresses some interesting issues that have affected the course of politics in Sarawak namely ethno-politics, strong-men politics, twenty-points agreement, and political disunity among the Iban.
Includes bibliographical references and index.
Keywords: Ethnology -- Malaysia -- Sarawak; Iban (Bornean people) -- Politics and government; Political culture -- Malaysia; Local government -- Sarawak; Sarawak -- Politics and government